Keratinocyte Binding Assay Identifies Anti-Desmosomal Pemphigus Antibodies Where Other Tests Are Negative - Giurdanella, Federica; Nijenhuis, Albertine M.; Diercks, Gilles F. H.; Jonkman, Marcel F.; Pas, Hendri H. (Frontiers in Immunology, 2018)
The serological diagnosis of pemphigus relies on the detection of IgG autoantibodies directed against the epithelial cell surface by IIF on monkey esophagus and against Dsg1 and Dsg3 by ELISA. Although being highly sensitive and specific tools, discrepancies can occur. It is not uncommon that sera testing positive by ELISA give a negative result by IIF and vice versa. This brings diagnostic challenges wherein pemphigus has to be ascertained or ruled out, especially when no biopsy is available. We utilized the ability of anti-Dsg3 and anti-Dsg1 IgG to bind in specific desmosomal patterns to living cells to investigate these discrepancies between IIF and ELISA. Living cultured primary normal human keratinocytes were grown under differentiating conditions to induce adequate expression of Dsg1 and Dsg3, incubated with patient serum for one hour, and then stained to visualize bound IgG. We investigated two different groups; sera from patients with a positive DIF and inconsistent serological findings (n=43) and sera with positive ELISA or IIF but with negative DIF (n=60). As positive controls we used 50 sera from patients who fulfilled all diagnostics criteria, and 10 sera from normal human subjects served as negative controls. In the DIF positive group IgG from 39 of the 43 sera bound to the cells in a desmosomal pattern while in the DIF negative group none of the 60 sera bound to the cells. This shows that for pemphigus patients ELISA and IIF can be negative while anti-desmosomal antibodies are present and vice versa that ELISA and IIF can be positive in non-pemphigus cases. In absence of a biopsy for DIF such findings may lead to misdiagnosis.